Rejuvenation of Ovarian Function after Autologous Platelet Lysate Injection: Promising Evidence from Confirmed Cases - Garavelas, Athanasios; Michalopoulos, Efstathios; Mallis, Panagiotis; Nikitos, Eros (Clinical Journal of Obstetrics and Gynecology, 2023)
Intraovarian injection of autologous Platelet Lysate (PL) can be considered a potential therapeutic strategy for ovarian function rejuvenation. Especially, in women diagnosed with Poor Ovarian Response (POR) or Primary Ovarian Insufficiency (POI), the exogenous administration of the autologous platelet-derived growth factors, influence positively the regulation of the serum Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), and Anti-Mullerian Hormone (AMH) and Estradiol (E2). Therefore, the evaluation of the serum levels of the aforementioned hormones was performed on 10 participants with a mean age of 43 ± 4 years diagnosed with POR or POI, who received intraovarian PL injection monotherapy. The monitoring of the serum hormone levels was performed for 3 months. The results of this study clearly showed that all participants were characterized by elevated levels of FSH and LH and reduced levels of E2 and AMH, prior to the PL injection. However, the levels of all hormones started to change after the 1st month of follow-up monitoring. Moreover, 40% of the participants conceived successfully either by natural way or after in vitro Fertilization (IVF). Considering these, the intraovarian injection of autologous PL exhibited promising evidence regarding the altering of hormone levels at physiological values. Moreover, the contained PL growth factors were implicated in angiogenesis promotion and also in toleration of the inflammatory microenvironment, regulating positively ovarian function. In conclusion, the intraovarian autologous PL injection is considered a safe, effective, and tolerable therapeutic strategy in women with POR or POI. Moreover, the results of this study were very encouraging, especially for the women with infertility issues, who want their genetic offspring.